2024
DOI: 10.21037/hbsn-22-579
|View full text |Cite
|
Sign up to set email alerts
|

Management of hepatocellular carcinoma recurrence after liver surgery and thermal ablations: state of the art and future perspectives

Astrid Herrero,
Cyprien Toubert,
Jose Ursic Bedoya
et al.

Abstract: Despite the improvements in surgical and medical therapy for hepatocellular carcinoma (HCC), recurrence still represents a major issue. Up to 70% of patients can experience HCC recurrence after liver resection (LR), as well as 20% of them even after liver transplantation (LT). The patterns of recurrence are different according to both the time and the location. Similarly, the risk factors and the management can change not only according to these patterns, but also according to the underlying liver condition an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 124 publications
0
2
0
Order By: Relevance
“…Recurrence is a major complication in the surgical treatment of patients with HCC. The risk factors for recurrence, the usefulness of adjuvant therapy to prevent recurrence, and the management of recurrence after resection have been investigated previously [17]. However, the prevention and management of recurrence are controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence is a major complication in the surgical treatment of patients with HCC. The risk factors for recurrence, the usefulness of adjuvant therapy to prevent recurrence, and the management of recurrence after resection have been investigated previously [17]. However, the prevention and management of recurrence are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The timing and location of recurrence are particularly related to prognosis. Herrero et al [17] reported that 12 months was the most useful cutoff time period to define early recurrence after surgery from recent larger multicenter studies [23,24]. Early recurrence commonly interacts with tumor-related factors such as AFP, tumor number, tumor size, poor differentiation, and vascular invasion [25,26].…”
Section: Discussionmentioning
confidence: 99%